Progreso de estadio y requerimiento de terapia de reemplazo renal en un programa de protección renal en Colombia. Estudio de cohorte. - Yepes Delgado, Carlos Enrique; Pérez Dávila, Sara; Montoya Jaramillo, Marcela; Orrego Orozco, Beatriz Elena (Nefrologia, 2017)
Background: Due to the global burden represented by chronic kidney disease (CKD), the World Health Organization encouraged the implementation of renal protection programmes (RPP) to affect its incidence through prevention and control measures. Objectives: To assess the effectiveness of a Colombian RPP in terms of its effect on the stage progression of CKD and the need for renal replacement therapy (RRT). Methods: An analytical study that monitored 2 cohorts of patients diagnosed with CKD. The study compares the behaviour of clinical and renal impairment indicators from patients exposed to a RPP with that of patients following conventional treatment (CT). The population of both intervention groups was considered when determining the sample size. The incidence rate was calculated as well as patient survival (Kaplan Meier). In addition, a multivariate analysis (Cox) was used to calculate the influence that exposure to the RPP had on the outcomes of the patients following the RPP and those following CT. Results: The patients exposed to the RPP took longer to advance to the next CKD stage and require RRT. The incidence rate for progression is higher for the patients following CT (0.050, IC 95%: 0.040-0.064) compared to those in the RPP (0.034, IC 95%: 0.030-0.039). The ratio of incidence rates was 1.480 (IC 95% 1.21-1.90). The hazard of progression was lower for the RPP (HR: 0.855, IC 95%: 0.74-0.98), as was the hazard of requiring RRT (HR: 0.797, IC 95%: 0.606-1.049). Conclusions: The RPP is a secondary prevention strategy against CKD which has an effect on the stage progression of CKD and the need for RRT. Early patient detection has a positive effect on the outcomes studied.